Low light acclimation strategy of the brown macroalga Undaria pinnatifida: Significance of lipid and fatty acid remodeling for photosynthetic competence. Issue 6 (7th October 2021) - Zhukova, Natalia V.; Yakovleva, Irina M.
Abstract : Brown macroalgae, being important components of benthic communities in temperate regions, are frequently subjected to light limitation. To extend our understanding of their low light acclimation strategies to the regulation of membrane lipid environment, photosynthetic characteristics, lipid class, fatty acid profiles and chloroplast ultrastructure were compared in Undaria pinnatifida (Phaeophyceae, Ochrophyta) after long‐term exposure to low and moderate light intensities (LL, 100 and ML, 280 µmol photons · m −2 · s −1 ). We show that light limitation significantly increased PSII quantum efficiency and photosynthetic electron transport rate, enhanced pigment contents and concentration of thylakoid membranes in chloroplasts but decreased the distance between the thylakoid stacks. These physiological alterations at LL were accompanied by a selective remodeling of thylakoid membrane lipids driven by increases in monogalactosyldiacylglycerol (MGDG) and phosphatidylglycerol (PG) contents. Light limitation also induced active production of PG specific trans ‐Δ 3 ‐hexadecenoic acid and accumulation of n−3 polyunsaturated fatty acids (PUFA) mostly in PG and MGDG at the expense of the rise in 18:3n−3 and 20:5n−3, 18:4n−3, respectively. These changes in lipid and FA profiles are apparently responsible for supporting thylakoid biogenesis and efficient photosynthesis at light limitation, thus contributing to photoacclimation strategies in brown algae. The content of triacylglycerols (TAG) and the level of their PUFA were decreased at LL, suggesting the consumption of TAG as a source of PUFA and energy reserves. Thus, U. pinnatifida is able to successfully overcome periods of low irradiance through the effective light harvesting and utilization that are provided by high flexibility of lipid biosynthesis.